Sources of trace elements in wet deposition in Pamukkale, Denizli, western Turkey. Issue 1 (2nd January 2017) - Cukurluoglu, Sibel
ABSTRACT: Forty-two rainwater samples were collected during December 2011 and November 2012 in Pamukkale, Denizli, Turkey to investigate the characteristics of trace elements in wet deposition. The samples were analyzed by inductively coupled plasma optical emission spectrometry. Zn, Al, and Fe concentrations contributed 50.4% to the total element concentration. The trace element concentrations in rainwater samples showed seasonal variations, with high and low values in spring and summer, respectively. The daily total trace element concentrations of rainwater samples decreased exponentially with increasing precipitation rates. The wet deposition fluxes of trace elements were more affected by precipitation heights than concentrations. Enrichment factor analysis showed that Cr, Ni, Mn, Cd, Zn, Pb, Cu, Li, Sr, Co, and Ba indicate anthropogenic enrichment, while Al, Fe, and Ti were considered to be of crustal origin. As a result of principal component analysis, a three-component system of precipitation consisted of a mixed component (crustal and anthropogenic), a local pollution component, and an anthropogenic component, which explains 86.5% of the total variance. A significant fraction of the measured anthropogenic pollutants was transported to the sampling area from source regions in the North Atlantic Ocean, northern Europe, and the Balkans based on back-trajectory analysis. The acidic rain events, high concentrations, and fluxes of trace elements obtained in this study show that wet deposition in Pamukkale may be crucial for impacts on the local travertine. Trace elements that reach travertine by wet deposition may be viewed as a risk because of the anthropogenic origins of air pollutants.